The impact of loneliness and fear of missing out in predicting phubbing behaviour among undergraduates in Malaysia - Ang, May Phing; Chong, Yuan Xin; Lau, Pei Jun (2019)
With the accompaniment of easy access to the internet, smartphones have become the primary tool for communication purposes in the daily lives of people. Smartphones have undeniably brought convenience not only in terms of communication but in many other aspects such as entertainment, information seeking and managing one’s life. However, despite the many benefits, frequent use of smartphones has caused individuals to develop unhealthy habits such as phubbing and this consequently raised questions about whether this act damages interpersonal relationships. Therefore, the purpose of this study is to investigate the factors that predict phubbing behaviour among undergraduate students in Malaysia namely loneliness and fear of missing out (FoMO). 173 undergraduate students across Malaysia were recruited for this study through convenient sampling by using an online survey. UCLA Loneliness Scale Version 3, Fear of Missing Out Scale (FoMOs) and Phubbing Scale (PS) were employed to measure the variables in our study. Findings of this study revealed that loneliness and FoMO significantly predicted phubbing behaviour. Moreover, results of multiple regression indicated that FoMO was the stronger predictor of the phubbing behaviour. As phubbing is not a widely researched topic in Malaysia, findings of this study can contribute to being a source of reference for awareness campaigns in the future. Furthermore, it also gives light to relevant professionals in developing behavioural interventions to prevent severe addiction that consequently gives rise to physiological and psychological health issues among individuals.